2023
DOI: 10.1186/s13054-023-04681-6
|View full text |Cite
|
Sign up to set email alerts
|

Instruments to assess post-intensive care syndrome assessment: a scoping review and modified Delphi method study

Nobuto Nakanishi,
Keibun Liu,
Akira Kawauchi
et al.

Abstract: Background The assessment of post-intensive care syndrome (PICS) is challenging due to the numerous types of instruments. We herein attempted to identify and propose recommendations for instruments to assess PICS in intensive care unit (ICU) survivors. Methods We conducted a scoping review to identify PICS follow-up studies at and after hospital discharge between 2014 and 2022. Assessment instruments used more than two times were included in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…These assessments were recently recommended to identify PICS. 31 Logistic regression analyses will be conducted to identify predictors for mental and cognitive impairments in the long term, whereby the independent variables are the HADS (cut-off >7 points) and the MoCA (cut-off <26 points for mild cognitive impairment). Dependent variables for mental and cognitive health include age, sex, delirium during ICU stay, previous mental health problems, duration of mechanical ventilation, multiple organ failure, primary disease and Comorbidity Index.…”
Section: Methodsmentioning
confidence: 99%
“…These assessments were recently recommended to identify PICS. 31 Logistic regression analyses will be conducted to identify predictors for mental and cognitive impairments in the long term, whereby the independent variables are the HADS (cut-off >7 points) and the MoCA (cut-off <26 points for mild cognitive impairment). Dependent variables for mental and cognitive health include age, sex, delirium during ICU stay, previous mental health problems, duration of mechanical ventilation, multiple organ failure, primary disease and Comorbidity Index.…”
Section: Methodsmentioning
confidence: 99%
“…In 2023, the Japanese Society of Intensive Care Medicine recommended 6‐min walk test, medical research council (MRC) score, and grip strength for physical functions, MoCA, Mini‐Mental State Examination (MMSE), and short memory questionnaire (SMQ) for cognitive function, HADS, IES‐R, and patient health questionnaire‐9 (PHQ‐9) for mental health, Barthel Index, Instrumental Activities of Daily Living (IADL), and Functional Independence Measure (FIM) for the activities of daily living, and Short Form‐36 (SF‐36), SF‐12, EQ‐5D‐5L, 3L, and VAS for quality of life. 70 The PICS assessment tools are summarized in Table 1 .…”
Section: Pics‐related Disordersmentioning
confidence: 99%
“…A recent study has discovered that often utilized tools for this purpose include the Hospital Anxiety and Depression Scale (HADS), Impact of Events Scale-Revised (IES-R), and the six-item Impact of Event Scale-6 (IES-6) [ 17 ]. However, by comparing all of the PICS assessment methods, it has been shown that the Montreal Cognitive Assessment (MoCA) achieved the highest score in terms of reliability and validity for assessing the cognitive function of patients after ICU admission [ 28 ]. A protocol was developed for a multicenter randomized controlled trial that aims to evaluate the effects of a post-ICU multidisciplinary follow-up on the quality of life [ 29 ].…”
Section: Reviewmentioning
confidence: 99%